Association between the Expression of Sexual Orientation and/or Gender Identity and Mental Health Perceptions in the Peruvian LGBTI Population - Castaneda, Jane (2023)
Introduction: The non-expression of sexual orientation and gender identity can affect mental health in the lesbian, gay, bisexual, transgender, and intersex population in Peru. Method: Secondary, observational, analytical, and cross-sectional analyses of data from the “First Virtual Survey on the LGBTI population” were conducted with a population (n = 11,345) of LGBTI adults aged 18 years old or more. The variables of mental health and expression of sexual orientation and/or gender identity were measured using a self-reported questionnaire that did not include a validated scale; questions with multiple alternatives that included “yes” and “no” options were used. Prevalence ratios (PR) and 95% confidence intervals (95% CI) were obtained by glm log Poisson regression models. Results: The median age of the participants was 25 years (IQR: 21–30), and the majority of the population identified as gay, followed by lesbian and bisexual. Individuals who expressed their sexual orientation and/or gender identity were 17% less likely to have had perceived mental health problems in the last 12 months (PR: 0.83, 95% CI: 0.76–0.90, p < 0.001). Conclusions: The non-expression of sexual orientation and/or gender identity has a significant negative effect on the mental health problems of the LGBTI population. These results highlight the importance of promoting the expression of sexual orientation and gender identity in our community.